1996
DOI: 10.1021/jf9508007
|View full text |Cite
|
Sign up to set email alerts
|

Singlet versus Triplet Reactivity in Photodegradation of C40 Carotenoids

Abstract: Direct observations of triplet excited states of astaxanthin (I), -carotene (II), canthaxanthin (III), and zeaxanthin (IV) in toluene at 25°C following unsensitized laser flash photolysis and using transient absorption spectroscopy have yielded the singlet-triplet intersystem crossing yields 3.7 × 10 -3 (I), 5.4 × 10 -4 (II), 9.7 × 10 -3 (III), and 1.8 × 10 -3 (IV), based on triplet-triplet extinction coefficients obtained in anthracene-sensitized experiments. A carbonyl rather than a hydroxy group distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 28 publications
8
24
0
1
Order By: Relevance
“…Results showed that the least amount of change in ∆ E was related to the sample (5.31 ± 0.03) with black lid and the sample covered with G/A‐TiO 2 ‐2% (6.16 ± 0.04), respectively (Table S2). On the other hand, without lid samples showed more changes in ∆ E (compared to with lid samples), which is probably due to more oxidation of pigments present in the oil, caused by oxygen transmission through the bilayer films (Nielsen et al ., ). However, the change of ∆ E decreased in samples covered with bilayer film containing low concentration of TiO 2 nanoparticles, which represents the lower UV light transmittance of bilayer films and the significantly lower change in the colour of fish oil caused by photooxidation (Christophersen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Results showed that the least amount of change in ∆ E was related to the sample (5.31 ± 0.03) with black lid and the sample covered with G/A‐TiO 2 ‐2% (6.16 ± 0.04), respectively (Table S2). On the other hand, without lid samples showed more changes in ∆ E (compared to with lid samples), which is probably due to more oxidation of pigments present in the oil, caused by oxygen transmission through the bilayer films (Nielsen et al ., ). However, the change of ∆ E decreased in samples covered with bilayer film containing low concentration of TiO 2 nanoparticles, which represents the lower UV light transmittance of bilayer films and the significantly lower change in the colour of fish oil caused by photooxidation (Christophersen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…21 Among the carotenoids, astaxanthin was found to be more effective than β-carotene as an antioxidant 22 and a better agent to destroy free radicals than other carotenoids. 23 The predominance of astaxanthin and its esters in the meat of the shrimps studied indicates that it is a good source of the natural antioxidant astaxanthin, which may provide some health benefits to consumers. Further, as it is also observed that the carotenoid extract from the waste of the four species of shrimp studied contains astaxanthin and its esters as major carotenoids, the waste can form a valuable source of natural carotenoid, which is available for recovery for subsequent use as a pigment source in aquaculture diets.…”
Section: Results and Discussion Carotenoids In Different Body Componentsmentioning
confidence: 97%
“…Researchers have reported that capsanthin, which contains 11 conjugated double bonds, a conjugated keto-group and a cyclopentane ring, had higher Antioxidant Properties of Carotenoids 105 ORDER REPRINTS antiphotooxidative activity than b-carotene, which has the same number of double bonds but neither of the functional groups (Chen et al, 1997;Nielsen et al, 1997).…”
Section: Singlet Oxygen-quenching Activity Of Carotenoids During Photmentioning
confidence: 99%